Prenatal Ionizing Radiation Exposure Effects on Cardiovascular Health and Disease in C57Bl Mice - Sreetharan, Shayenthiran (My University, 2017)
Ionizing radiation exposure during pregnancy raises concerns of potentially harmful effects for both the mother and the unborn child. Fetal programming involves permanent changes in offspring phenotype due to stress experienced in-utero. This phenomenon has been well characterized in cardiometabolic disorders such as hypertension. The effects of prenatal ionizing radiation exposure on offspring cardiovascular endpoints following birth were studied in a mouse model. Pregnant wildtype C57Bl/6J mice were irradiated on day 15 of pregnancy with whole-body 137Cs gamma radiation at nominal doses of 5, 10, 50, 100, 300 or 1000 mGy. Post-natal measurements of offspring weight and blood pressure were completed. In female pups, blood pressure was significantly increased at 300 mGy and heart rate significantly decreased at 1000 mGy. Female pups were growth restricted over the study period at 50, 100 and 1000 mGy. Growth restriction in male pups was only observed at the highest dose of 1000 mGy. Unintended effects on the study measures caused by transportation of pregnant mothers to the irradiation facility were most evident in male offspring with increased blood pressure and heart rate and decreased body size. These unintended effects caused by transportation may have been attenuated with the 10 mGy in-utero exposure. Overall, these results suggest that prenatal radiation effects in mice are both dose- and gender-dependent, with even fairly low doses demonstrating (potentially adaptive) effects. There is a need for further study to better characterize the mechanism of this response.
Keywords: Ionizing radiation; Mouse; Blood pressure; Fetal programming; Developmental programming; Cardiovascular; Maternal stress; Transportation stress